2016
DOI: 10.1002/esp.4049
|View full text |Cite
|
Sign up to set email alerts
|

Normal fault growth and linkage in the Gediz (Alaşehir) Graben, Western Turkey, revealed by transient river long‐profiles and slope‐break knickpoints

Abstract: The Gediz (Alaşehir) Graben is located in the highly tectonically active and seismogenic region of Western Turkey. The rivers upstream of the normal faultbounded graben each contain a nonlithologic knickpoint, including those that drain through inferred fault segment boundaries. Knickpoint heights measured vertically from the fault scale with footwall relief and documented fault throw (vertical displacement). Consequently, we deduce these knickpoints were initiated by an increase in slip rate on the basinbound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(80 citation statements)
references
References 88 publications
5
75
0
Order By: Relevance
“…Detrital apatite fission track data show that the southern margin of the Gediz Graben experienced two major exhumation events, one involving the whole margin during late Miocene and one involving only its western part (Salihli area) during Plio‐Quaternary times, thus generating a differential uplift of this sector (Asti et al, ). This differential exhumation is consistent with the differential evolution of slip rates on faults bounding the southern margin of the modern graben in response to fault segments interaction and linkage (Kent et al, , ).…”
Section: Geological Settingsupporting
confidence: 80%
See 1 more Smart Citation
“…Detrital apatite fission track data show that the southern margin of the Gediz Graben experienced two major exhumation events, one involving the whole margin during late Miocene and one involving only its western part (Salihli area) during Plio‐Quaternary times, thus generating a differential uplift of this sector (Asti et al, ). This differential exhumation is consistent with the differential evolution of slip rates on faults bounding the southern margin of the modern graben in response to fault segments interaction and linkage (Kent et al, , ).…”
Section: Geological Settingsupporting
confidence: 80%
“…Another possibility to explain the localization of the Plio‐Quaternary exhumation event deals with the evolution of faulting at the southern margin of the basin. Kent et al (, ) showed that active fault segments bounding the southern margin of the modern Gediz Graben became connected during the last 2.6–2 Myr, thus resulting in an increase in throw rates along the Salihli segment of this fault system. This increase in throw rate might have also played a role in the differential exhumation of the Gediz detachment in the Salihli area.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have exploited these evolutionary characteristics of normal fault systems to assess the geomorphic response to step changes in the rate of local rock uplift (Boulton and Whittaker, 2009;Whittaker and Boulton, 2012;Whittaker and Walker, 2015;Kent et al, 2016). Following these previous studies and based on the observation that the Ptolemy and South-Central Crete faults linked in the geologically recent past (< 1 Ma), we infer that along the Tsoutsouros section of the fault uplift rates increased rapidly following linkage.…”
Section: Relationships Between Fault Growth Linkage and Footwall Upmentioning
confidence: 74%
“…Along-strike, slip and slip rates parabolically decay from a maximum near the fault center to zero at fault tips (e.g., Bürgmann et al, 1994;Cowie & Scholz, 1992;Dawers et al, 1993;Manighetti et al, 2001;Roberts & Michetti, 2004). Such distribution of slip and slip rates controls the geometry and geomorphic evolution of along-footwall topography and river catchments (e.g., Densmore et al, 2004Densmore et al, , 2005Kent et al, 2016;Roda-Boluda & Whittaker, 2017). Across-strike, uplift and uplift rates exponentially decay from maxima near the fault to zero a few tens of kilometers away (e.g., King et al, 1988;King & Ellis, 1990;Thompson & Parsons, 2016).…”
Section: Working Framework and Hypothesesmentioning
confidence: 99%